2008
DOI: 10.1103/physrevc.77.034313
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial projected shell model study of γ-vibrational bands in even-even Er isotopes

Abstract: We expand the triaxial projected shell model basis to include triaxially deformed multi-quasiparticle states. This allows us to study the yrast and γ -vibrational bands up to high spins for both γ -soft and well-deformed nuclei. As a first application, a systematic study of the high-spin states in Er isotopes is performed. The calculated yrast and γ bands are compared with the known experimental data, and it is shown that the agreement between theory and experiment is quite satisfactory. The calculation leads … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…All these interaction strengths are the same as those used in our earlier studies for the even-even nuclei in the same mass region [3,22,23,24]. Thus, we have a consistent description for doubly-even and doubly-odd nuclear systems.…”
mentioning
confidence: 90%
“…All these interaction strengths are the same as those used in our earlier studies for the even-even nuclei in the same mass region [3,22,23,24]. Thus, we have a consistent description for doubly-even and doubly-odd nuclear systems.…”
mentioning
confidence: 90%
“…The purpose of the present work is to investigate the highspin properties of 76 Ge using the multi-quasiparticle (qp) triaxial projected shell model (TPSM) approach [13][14][15][16][17]. In the SSM analysis, the primary emphasis was on the low-lying states and the present investigation complements the results obtained by the SSM approach.…”
Section: Introductionmentioning
confidence: 97%
“…It has been demonstrated to provide excellent description of the observed properties [33][34][35][36]. In a more recent development, this model has been extended to study the observed band structures in odd-odd 128 Cs nucleus and it has been shown to reproduce the properties of chiral bands quite well, in particular, the observed trend of B(E2) transition probabilities [36].…”
mentioning
confidence: 97%